STRATEGI PEMBELAJARAN INOVATIF PENDIDIKAN AGAMA ISLAM DENGAN MEDIA POWERPOINT DALAM MENINGKATKAN MUTU PENDIDIKAN DI SMP NEGERI 3 MATTIROBULU - Hermanto, Hermanto (Department of Islamic Education Management, 2022)
Abstract: This research was conducted with the aim of uncovering, analyzing and explaining learning strategies and utilizing PowerPoint media implemented by Islamic religious education teachers in delivering learning materials in the Integrated and the Special Program Bayat. This type of research is field research using a qualitative descriptive approach. The results show that SMPN 3 Mattirobulu have implemented the 2013 curriculum. Among the teacher roles shown in the two schools were the teacher as a planner, manager, implementer, and evaluator. Also, the teacher plays the role of transferring knowledge, fostering noble morals, mediators and facilitators. Supporting factors is the ability of teachers to operate computers, the availability of media resources, computer-based facilities, and infrastructure in schools, support from the head school, and the conducive condition of the school environment and the culture of mutual help to help those who are built are quite strong. The inhibiting factor is the lack of familiarity of teachers in using PowerPoint media in the learning process, the preparation time is still limited, and the number of computer-based facilities and infrastructure is still limited as well. Abstrak: Penelitian ini dilaksanakan dengan tujuan untuk mengungkap, menganalisis dan menjelaskan strategi pembelajaran dan pemanfaatan media powerpoint yang diterapkan guru pendidikan agama Islam dalam menyampaikan materi pembelajaran di SMP Negeri 3 Mattirobulu Program Khusus Bayat. Jenis Penelitian ini adalah penelitian lapangan (field research) dengan menggunakan pendekatan deskriptif kualitatif. Hasil yang diperoleh adalah sekolah telah menerapkan kurikulum 2013. Di antara peranan guru yang ditunjukkan di kedua sekolah tersebut adalah guru sebagai perencana, pengelola, pelaksana dan evaluator. Selain itu, guru juga berperan sebagai pentransfer ilmu, pembina akhlak mulia, mediator dan fasilitator. Faktor pendukung program adalah kemampuan guru dalam mengoperasikan komputer, ketersediaan sumber media, sarana dan prasarana berbasis komputer di sekolah, dukungan dari kepala sekolah, dan kondisi lingkungan sekolah yang kondusif serta budaya saling tolong menolong yang terbangun cukup kuat. Faktor penghambatnya adalah kurang terbiasanya guru dalam menggunakan media powerpoint dalam proses pembelajaran, waktu persiapan dan jumlah sarana dan prasarana berbasis komputer yang masih terbatas.